2022
DOI: 10.3390/su14031211
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Disabled People in Environmental-Education-Focused Academic Literature

Abstract: Environmental education (EE) is a lifelong process to acquire knowledge and skills that can influence pro-environmental behavior, environmental activism, and disaster-risk management. Disabled people are impacted by environmental issues, environmental activism, and how EE is taught. Disabled people can be learners within EE but can contribute to EE in many other roles. Given the importance of EE and its potential impact on disabled people—and given that equity, diversity, and inclusion is an ever-increasing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 102 publications
(201 reference statements)
0
15
0
Order By: Relevance
“…However, activities based on individual EDI concepts have limitations, so EDI phrases and policy and action frameworks containing more than one concept [79,80,[124][125][126][127][128] are increasingly employed to better the situation for members of marginalized groups such as women, Indigenous Peoples, visible minorities, racialized minorities, disabled people, people with disabilities, and LGBTQ2S+ [80,129] (for disability terms, see [130] (p. 38)). EDI, as a phrase, is also used in conjunction with environmental issues [131][132][133][134][135][136].…”
Section: Environment and Edimentioning
confidence: 99%
See 4 more Smart Citations
“…However, activities based on individual EDI concepts have limitations, so EDI phrases and policy and action frameworks containing more than one concept [79,80,[124][125][126][127][128] are increasingly employed to better the situation for members of marginalized groups such as women, Indigenous Peoples, visible minorities, racialized minorities, disabled people, people with disabilities, and LGBTQ2S+ [80,129] (for disability terms, see [130] (p. 38)). EDI, as a phrase, is also used in conjunction with environmental issues [131][132][133][134][135][136].…”
Section: Environment and Edimentioning
confidence: 99%
“…Regarding views on-and perception of environmental activism, stewardship, action and governance, many studies have engaged with the theme of students as activist [137], and environmental education focuses on how to teach students to gain knowledge [131] and to instill [138][139][140][141] and predict [142][143][144] environmentally responsible behavior, including on campus [145][146][147]. Studies have reported on educating students on action-related strategies [138,[148][149][150][151][152], instilling action in students [139,140,, and predicting action [175,182,183].…”
Section: Environmental Activism and Studentsmentioning
confidence: 99%
See 3 more Smart Citations